PROGRAM PEMBENTUKAN DAN PENGEMBANGAN WIRAUSAHA BERBASIS ICT DI FAKULTAS SAINS DAN TEKNOLOGI (FST), UNIVERSITAS AL AZHAR INDONESIA (UAI) - Parwati, Niken; Tanjung, Widya Nurcahayanty; Safitri, Riri; Astharini, Dwi (Jurnal Pengabdian dan Kewirausahaan, 2018)
ABSTRACTEntrepreneurship initiating and development program as a supporter of university programs as an enterprising university is designed to produce new entrepreneurs from FST UAI students and alumni. The activity plan starts from initial mapping, training, strengthening and launching. Preliminary Mapping takes SWOT measurements to map current tenants' strengths and weaknesses, to maximize opportunities and minimize threats that also accompany them. Followed by the trainings in seven parts, namely, business planning, financial planning, marketing management, E-Commerce, product development, Branding, IPR, and Muslimpreneur. Strengthening Phase 1 is the FGD regarding improvements and innovations, expansion and diversification, efficiency and utilization. In strengthening phase 2 there was discussion of real problems faced by tenants. The activity ended with the launch of 6 new ICT-based entrepreneurs per year and the publication of results. Keywords: entrepreneur, syariah, ICT, UAI